1964
DOI: 10.1037/h0043928
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the importance of S-R spatial continguity for proficient primate discrimination performance.

Abstract: 2 groups of 8 rhesus monkeys were presented a difficult pattern discrimination task under conditions of spatial contiguity (C) and discontiguity (D) of discriminative stimulus and instrumental response in the order C-D-C for Group A, and D-C-C for Group B. Group A asymptotically learned under initial C condition, whereas Group B did not learn under initial D condition; when switched, Group A performed discriminations very poorly under D, while Group B began to learn under C; the groups performed identically we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

1966
1966
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 14 publications
1
29
0
2
Order By: Relevance
“…He argues that goal tracking may be regarded as a form of consummatory responding and sign tracking as a form of preparatory behavior (1979). "Two-phase" responses were also observed in monkeys when presented with discrimination problems in which the discrimination stimulus was spatially discontiguous with the site of the instrumental response (Polidora & Fletcher, 1964;Polidora & Thompson, 1965). The monkeys invariably looked at the site of the stimulus and touched it before executing the required instrumental response.…”
Section: Autoshapingmentioning
confidence: 93%
“…He argues that goal tracking may be regarded as a form of consummatory responding and sign tracking as a form of preparatory behavior (1979). "Two-phase" responses were also observed in monkeys when presented with discrimination problems in which the discrimination stimulus was spatially discontiguous with the site of the instrumental response (Polidora & Fletcher, 1964;Polidora & Thompson, 1965). The monkeys invariably looked at the site of the stimulus and touched it before executing the required instrumental response.…”
Section: Autoshapingmentioning
confidence: 93%
“…showing that spatial contiguity affects non-social associative learning in animals (Kushnir & 591 Gopnik, 2007;Polidora & Fletcher, 1964;Wasserman & Miller, 1997). However, differing 592 success levels between children in the demonstration and no-demonstration conditions 593 indicated that the reward location during demonstration did affect their success.…”
Section: Convergent Behavioral Patterns 569mentioning
confidence: 99%
“…The experimental history of each S was identical (Harlow, Harlow, Rueping, & Mason, 1960;Polidora & Fletcher, 1964;Polidora & Thompson. 1964;Polidora, 1965b;Polidora & Thompson, 1965), and they were thus uniformly test-sophisticated.…”
Section: Methods Subjectsmentioning
confidence: 99%